Literature review of post‐traumatic stress disorder in the critical care population. Issue 11 (24th April 2016) - Morrissey, Matthew; Collier, Elizabeth
Abstract : Aim: To determine which factors relate to the development of post‐traumatic stress disorder, in adult patients who are admitted to critical care units. Background: Patient survival rates from critical care areas are improving each year and this has led to interest in the long‐term outcomes for patients who have been discharged from such environments. Patients typically require invasive and extensive treatment, which places a stress on physical and mental health. Prevalence estimates of post‐traumatic stress disorder in the critical care discharge population vary from 5–63%, yet it remains unclear what the predisposing factors are. Design: A systematised review. Method: Subject heading and keyword searches were conducted in MEDLINE, CINAHL, PsycINFO and ScienceDirect, with 23 articles identified that examined the relationship between critical care and the development of post‐traumatic stress disorder. Results: Three main themes were identified; Critical Care Factors, Patient Factors and Experience Factors. Eight key and three potential causative factors were found: younger age, female, previous psychiatric history, length of ICU stay, benzodiazepine sedation, use of stress hormones, delusional memory and traumatic memory, delirium, GCS score of ≤9 on admission & use of mechanical restraint. Conclusions: Post‐traumatic stress reactions can be strongly related to the development and presence of traumatic and delusional memories. Younger patients may exclude themselves from research to avoid their traumatic thoughts. The role of prior psychiatric illness is unknown. Distinction between 'factual' and 'false' or delusional memory as occurs in the literature maybe unhelpful in understanding trauma reactions. Relevance to clinical practice: There are around 38, 000 occupied critical care beds each year in England. The scale of the issue is therefore substantial. Risk factors can be isolated from available evidence and provide a rudimentary risk assessment tool to inform practice development in this area.